Dead Wood: Key to Enhancing Wildlife Diversity in Forests - Holly K. Ober; Patrick J. Minogue (EDIS, 2007)
WEC238, a 6-page illustrated fact sheet by Holly K. Ober and Patrick J. Minogue, explains how snags, logs, and brush piles provide important resources for wildlife, how these habitat elements can be created, and how much dead wood to provide. Includes references. Published by the UF Department of Wildlife Ecology and Conservation, July 2007.